2016
DOI: 10.21037/sci.2016.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylating agents after allogeneic blood stem cell transplantation

Abstract: Allogeneic blood stem cell transplantation (allo-SCT) is a potentially curative treatment for patients with myeloid malignancies such as acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS), but relapse remains the major cause of treatment failure. So far, therapeutic options for patients with AML or MDS who relapse after allo-SCT generally consisted of palliative care, low-dose or intensive chemotherapy as well as cellular therapies such as donor lymphocyte infusions (DLI) and second transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
14
0
3
Order By: Relevance
“…A pre-emptive approach with cellular therapy [16], or with azacytidine [17], is one option, but requires close monitoring of a marker for minimal residual disease (MRD). Post-transplant prophylaxis of relapse is another possibility, as shown in a German cooperative study with panobinostat [18], or again with azacytidine [19][20][21][22]. Salvage strategies may need to be personalized in haploidentical graft recipients, as relapse can occur with loss of the HLA mismatched haplotype [23].…”
Section: Discussionmentioning
confidence: 99%
“…A pre-emptive approach with cellular therapy [16], or with azacytidine [17], is one option, but requires close monitoring of a marker for minimal residual disease (MRD). Post-transplant prophylaxis of relapse is another possibility, as shown in a German cooperative study with panobinostat [18], or again with azacytidine [19][20][21][22]. Salvage strategies may need to be personalized in haploidentical graft recipients, as relapse can occur with loss of the HLA mismatched haplotype [23].…”
Section: Discussionmentioning
confidence: 99%
“…77 A combination of a hypomethylating agent and DLI is safe with no apparent increase in GvHD or infection risk compared to DLIalone. 78,79 In a prospective study using azacitidine with DLI for relapsed disease after HLA-matched allo-HCT, the CR rate was 23% and the 2-year OS was 17%. 80 Another retrospective study utilizing decitabine followed by DLI for relapsed myeloid malignancies showed an overall response rate of 25% with 2-year OS of 11%.…”
Section: Combination Of Systemic Therapies With Donor-lymphocyte Infumentioning
confidence: 99%
“…Skuteczność HMAs w leczeniu nawrotu AML po allo-HSCT wykazano w wielu badaniach (tab. 1) [66][67][68][69][70][71][72][73]. Większość opublikowanych wyników dotyczy azacytydyny.…”
Section: Rola Azanukleotydów W Allo-hsctunclassified
“…W innym badaniu Schroeder i wsp. [67] przeprowadzili analizę retrospektywną 154 chorych z nawrotem choroby po allo-HSCT, Kamil Wiśniewski, Joanna Góra-Tybor, Leki wpływające na mechanizmy epigenetyczne w AML w tym 128 pacjentów z AML. U większości pacjentów (93%) podanie azacytydyny stanowiło pierwszą interwencję po nawrocie choroby.…”
Section: Rola Azanukleotydów W Allo-hsctunclassified
See 1 more Smart Citation